EDUCATION FOR CRITICAL CONSCIOUSNESS: A PANACEA FOR ETHNOCENTRISM IN NIGERIA - Mwajim, Ahmed U.; Dugje, Kadiri (Sokoto Educational Review, 2020)
Ethnicity is a strong belier base on cultural sentiment. This belief do not allow person to appreciate others, it block the believer front being reasonable and objective toward trying to evaluate other ethnic groups. These sentiments are most nursed by our political leaders for the purpose of achieving their personal interests. But such positions are detrimental to the unity, progress and development of our societies and communities, especially in Nigeria situations where many crises had resulted into lost of properties and lives. Hence the need to call for educational programme that will create or develop critical consciousness of our citizens, to be able to withstand the ethnic calls of our self-directed leaders. This type of education should reflect issues of critical thinking, analysis, judgment, negotiation and so on. This will develop or cultivate in our citizens the habits of assessing their situations before taking decision.